Spiritualitas Islam dalam Pengelolaan Keuangan Negara: Islamic Spirituality in State Financial Management - Subekan, Achmat; Azwar, Azwar (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
Citizenship is a legal status connecting individuals to a country, encompassing rights, obligations, identity, and protection. This study evaluates the impact of citizenship status on economic access and socio-economic inequality in Indonesia, focusing on disparities in well-being and economic opportunities. The research employs a normative legal method with approaches including legislation, case studies, conceptual, historical, and comparative analyses. The results show that citizenship inequality creates significant gaps in income, quality of life, and access to services. Individuals with full citizenship have better access to jobs and education compared to those with limited citizenship or no citizenship. This study recommends more inclusive policy reforms to reduce inequality and improve access for individuals with limited citizenship. The findings aim to assist academics and policymakers in designing strategies to enhance community well-being.